Chemical and Functional Properties of Cavendish Jepara 30 (Musa cavendishii) Banana Pseudostem Flour after Blanching and Soaking in Sodium Bisulphite Solution - Yuliatmoko, Welli; Murdiati, Agnes; Pranoto, Yudi; Marsono, Yustinus (Pakistan Journal of Nutrition, 2019)
Background and Objectives: Cavendish Jepara 30 (Musa cavendishii ) banana pseudostem in Indonesia is very abundant and has not been utilized because it is considered to be waste. The pseudostem contains dietary fibre, resistant starch (RS) and antioxidants that are strongly affected by several factors such as plant varieties and processing techniques. This study was conducted to investigate the effect of blanching and soaking in sodium bisulphite solution on changes in dietary fibre, resistant starch, antioxidants and the functional properties of Cavendish Jepara 30 banana pseudostem flour. Materials and Methods: Banana pseudostem of Cavendish Jepara 30 varieties were obtained from PT. Nusantara Tropical Farm Central Lampung, Indonesia. Preparation of the banana pseudostem flour included a blanching treatment at a temperature of 100°C for 10 min or soaking in 1% sodium bisulphite solution for 90 min. Results: The blanching treatment significantly increased the amount of soluble fibre by 3.55%, RS by 10.33%, total phenolic acids by 11.19 mg/100 g and antioxidant activity by 6.15% radical scavenging activity (RSA) but decreased the amount of insoluble fibre by 5.78%. The soaking treatment significantly increased the RS by 9.38% and the antioxidant activity by 12.5% RSA but decreased the insoluble fibre by 6.87%, the total fibre by 6.42% and the total phenolic acids by 17.52 mg/100 g. The blanching treatment also significantly increased the water holding capacity by10.81%, the swelling capacity by 13.87% and the cation exchange capacity was 9.75 meq kg–1. The microscopic structure of the flour after the blanching treatment was more porous and hollower than the natural pseudostem flour. Conclusion: Blanching treatment significantly increased the soluble fibre, RS, total phenolic acid content, antioxidant activity, water holding capacity, swelling capacity and cation exchange capacity of banana pseudostem flour. Blanching had no effect on the oil holding capacity of flour.